EBSERH E TRABALHO NA SAÚDE PÚBLICA: impactos da privatização da gestão do HUUFMA sobre as condições e relações de trabalho. - SILVA, Enaire de Maria Sousa da (2021)
This dissertation has as its object the study of the reflexes caused in the working conditions and relationships of those who work in the provision of health services at HU-UFMA, by privatizing the management of the Hospital by EBSERH. To this end, this work is structured in three chapters, so that the first two bring discussions regarding the current model of capitalist accumulation and its impacts on the labor scenario, as well as the reorganization of the Brazilian State from the 1990s, and its reflections on the country's Public Health Policy, respectively. The third chapter refers to a data collection carried out by applying a semi-structured interview script to health professionals who work at HU-UFMA. The interviewed professionals correspond to the categories of Dentistry, Physiotherapy, Social Work, Occupational Therapy, Nutrition, Speech Therapy, Pharmacy, Nursing and Psychology. Considering the ethical prerequisites for conducting the research, the project was previously submitted to the UFMA Research Ethics Committee (CEP), in compliance with Resolution 466/12 of the National Health Council of the Ministry of Health, a since speeches from health professionals were used for the composition of the study.